Reflective Thinking Process Students with Visual Learning Style in Mathematical Problem Solving (International Journal of Scientific Research and Management (IJSRM), 2020)
The student’s thought process is very dependent on each student’s learning style. One model of learning styles is visual learning styles. Students who have a visual learning style tend to more easily absorb information and learn by what they see. Most students do not recognize the type of learning style, so students are not able to optimize the process of absorbing mathematical information properly and result in a lack of mathematical reflective thinking abilities. Reflective thinking is a thought process that is needed in mathematical problem solving. The teacher must know the students’ mathematical reflective thinking process, so that it can help students in solving mathematical problems. The purpose of this study was to determine the reflective thinking process of students who have a visual learning style in solving mathematical problems. This research method is descriptive with a qualitative approach. The subjects in this study were 1 student of Meureudue 1 Junior High School who was selected based on a learning style questionnaire. Data collection is done through reflective thinking tests and interviews. The data obtained were analyzed using data reduction, data presentation and drawing conclusions. The results showed that the reflective thinking process of students who had a visual learning style on the Reacting indicator students began by mentioning what was known and asked, then on the Comparing indicator students identified the methods / concepts that were considered effective and connected the problems that were asked with the problems they had faced and the indicators. Contemplating students solve problems in questions and make conclusions but visual students are less clear in making conclusions and kinesthetic students still have incorrect calculations.